High-flexibility low-smoke fire-fighting power cable and preparation method thereof
By using composite materials in the outer sheath layer of flexible power cables, including methylvinyl silicone rubber, modified boron nitride nanosheets, graphene oxide and modified magnesium hydroxide, the problems of heavy metal pollution and fire smoke in existing cables are solved, and cables with high flexibility, low smoke, thermal conductivity and flame retardant properties are achieved, suitable for fire protection occasions.
Patent Information
- Application Number
- CN202510115880.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wire and cable manufacturing, and in particular to a highly flexible, low-smoke fire-fighting power cable and a preparation method thereof. Background Art
[0002] Cables are used as transmission devices for electrical energy or signals, and are usually composed of several or several groups of wires. Cables can be divided into rigid cables and flexible cables. Rigid cables have stronger impact resistance due to external protective components, while flexible cables can be applied to more cable laying scenarios due to their high flexibility.
[0003] At present, the outer sheath of flexible power cables is generally made of polyvinyl chloride and polyethylene materials, among which polyvinyl chloride accounts for 80% of the materials of wires and cables. Although polyvinyl chloride has good flame retardant properties, on the one hand, most materials in the stability and lubrication system of polyvinyl chloride cable materials also contain harmful heavy metal elements such as lead, barium, and cadmium. During the use of wires and cables, harmful heavy metal elements will gradually dissolve and flow into rivers and soil, causing permanent environmental pollution; on the other hand, in most fire accidents, the fire is caused by a short circuit in the wires and cables, and the insulating material polyvinyl chloride produces toxic gases such as hydrogen chloride and intense smoke during the combustion process, causing deaths and injuries.
[0004] Therefore, there is an urgent need to develop a low-smoke, environmentally friendly cable material for the outer sheath of flexible power cables to meet market demand. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present application provides a highly flexible and low-smoke fire-fighting power cable and a preparation method thereof. The outer sheath layer prepared by the present application has excellent mechanical strength, high toughness, thermal conductivity, high temperature resistance and flame retardancy, and also has a good smoke suppression effect. The prepared wires and cables are suitable for fire-fighting power supply occasions, which is beneficial for firefighters to carry out rescue work in emergency situations.
[0006] In the first aspect, the present application provides a highly flexible low-smoke fire-fighting power cable, which adopts the following technical solution: A highly flexible low-smoke fire-fighting power cable comprises, from the inside to the outside, a cable core, a shielding layer and an outer sheath layer; the cable core is made by coating a copper core with a low-density polyethylene film; the shielding layer is made by coating the cable core with aluminum foil; the outer sheath layer comprises the following raw materials by mass: 60-65 parts of methyl vinyl silicone rubber, 12-15 parts of ethylene propylene rubber, 8-10 parts of linear low-density polyethylene, 5-6 parts of a cross-linking agent, 20-22 parts of a flame retardant, 6-8 parts of a reinforced flame-retardant filler, 20-25 parts of a modified thermally conductive filler, 1.2-1.5 parts of a coupling agent, 1.3-1.5 parts of an antioxidant, 3-3.5 parts of a lubricant, 2-2.5 parts of a vulcanizing agent, and 0.6-0.8 parts of an accelerator, wherein the modified thermally conductive filler comprises modified boron nitride nanosheets, nanocellulose and graphene oxide; and the flame retardant is modified magnesium hydroxide.
[0007] By adopting the above technical scheme, the copper core is coated with low-density polyethylene film: providing basic electrical conductivity and certain mechanical strength. Aluminum foil shielding layer: used to shield electromagnetic interference and protect the signal in the cable from interference from external electromagnetic fields. Outer sheath layer: Methyl vinyl silicone rubber: providing good flexibility and temperature resistance. EPDM rubber: enhancing the elasticity and anti-aging properties of the material. Linear low-density polyethylene: providing mechanical strength and processing performance. Cross-linking agent: used to cross-link the rubber molecular chain to improve the heat resistance and mechanical properties of the material. Flame retardant: modified magnesium hydroxide to improve the flame retardant properties of the material. Enhanced flame retardant filler: zirconium oxide fiber matrix, providing additional mechanical strength and flame retardant properties. Modified thermal conductive filler: including modified boron nitride nanosheets, nanocellulose and graphene oxide, improving the thermal conductivity and flame retardant properties of the material. Coupling agent: improving the interface interaction between the filler and the matrix. Antioxidant: preventing the material from oxidative aging during processing and use. Lubricant: improving the processing performance of the material and reducing friction during processing. Vulcanizing agent: used in the vulcanization process of rubber to improve the mechanical properties and temperature resistance of the material. Accelerator: accelerates the vulcanization process and improves the vulcanization efficiency. Through the preparation method of this composite material, the cable can achieve high flexibility, low smoke, high thermal conductivity, high temperature resistance and excellent flame retardant properties, making it suitable for the special needs of fire power supply occasions.
[0008] Preferably, the method for preparing the modified magnesium hydroxide comprises the following steps: S21. According to the mass fractions, 100 parts of magnesium hydroxide, 100 parts of titanium isopropoxide, 7 parts of sodium dodecyl sulfate and 6 parts of ammonia water are placed in 400 parts of distilled water and mixed, and stirred at 25° C. for 1-2 hours in a reactor, and then heated to 60° C. at a rate of 4-6° C. / min, and continued to stir and react for 4-6 hours, and cooled and filtered; then calcined at 200° C. for 2 hours in a muffle furnace, and cooled to room temperature to obtain a solid A with porous titanium dioxide nanoparticles in situ grown on the surface of magnesium hydroxide; S22. According to the mass fractions, 150 parts of solid A are placed in a reactor with nitrogen protection, 200 parts of tetrahydrofuran are added and stirred for 2-3 hours, then 100 parts of diphenylphosphinoyl chloride tetrahydrofuran solution with a concentration of 0.05 g / mL is added dropwise at a rate of 15 mL / min, the temperature is raised to 53°C at a rate of 4°C / min, stirring and reacting are continued for 7 hours, cooled and filtered, and dried to obtain modified magnesium hydroxide.
[0009] By adopting the above technical scheme, porous titanium dioxide nanoparticles are first grown in situ on the surface of magnesium hydroxide through a sol-gel reaction. Then, the obtained solid A is stirred in tetrahydrofuran and a tetrahydrofuran solution of diphenylphosphinoyl chloride is added dropwise for reaction, and finally modified magnesium hydroxide is obtained. By growing porous titanium dioxide nanoparticles in situ on the surface of magnesium hydroxide, the number of hydroxyl groups on the surface of magnesium hydroxide and the number of sites for reaction with diphenylphosphinoyl chloride are increased, thereby increasing the grafting rate of diphenylphosphinoyl chloride. The modified magnesium hydroxide can significantly improve the flame retardant and smoke suppression properties of the outer sheath layer. The modified magnesium hydroxide can well connect adjacent boron nitride nanosheets to form a smoother heat conduction path. This synergistic effect not only enhances the thermal conductivity, but also improves the high temperature resistance and flame retardant properties. In summary, the modified magnesium hydroxide plays a key role in the preparation process of the outer sheath layer of the cable. Through its unique modification method and synergistic effect, the flame retardant, thermal conductivity and high temperature resistance of the cable are significantly improved. At the same time, this preparation method of modified magnesium hydroxide also reflects its application value and potential in materials science.
[0010] Preferably, the method for preparing the reinforced flame retardant filler comprises the following steps: S31, according to the mass fraction, placing 10 parts of zirconia fiber in 500 parts of xylene, ultrasonically dispersing for 30 minutes, adding 10 parts of glycine, refluxing for 12 hours, filtering, washing and drying to obtain pretreated zirconia fiber; S32. According to the mass proportions, place 10 parts of pretreated zirconia fibers in 500 parts of tetrahydrofuran, ultrasonically disperse for 40-50 minutes, ice-bath at 0°C, add 8 parts of diethyl 2-bromoethylphosphonate and 0.8 parts of N,N-diethylethylamine, stir well for 6-7 hours, filter, wash and dry to obtain the reinforced flame retardant filler.
[0011] By adopting the above technical scheme, first, the zirconia fiber is ultrasonically dispersed in xylene to make it uniformly dispersed. Then, glycine is added for reaction, and glycine reacts with the hydroxyl group on the surface of the zirconia fiber to form an amino group. This step is mainly for surface modification of the zirconia fiber. The pretreated zirconia fiber is dispersed in tetrahydrofuran again, and then diethyl 2-bromoethylphosphonate and N,N-diethylethylamine are added. The reaction is carried out under ice bath conditions, the purpose of which is to graft diethyl 2-bromoethylphosphonate to the surface of the zirconia fiber. This step is mainly to form a reinforced flame retardant filler with flame retardant properties. The prepared reinforced flame retardant filler can be uniformly dispersed in the composite material. When the outer sheath layer is impacted and cracks are generated, these fillers can withstand the external load like a bridge, and bridge between the cracks, consume the external load to do work, thereby improving the toughness of the outer sheath layer. The presence of the enhanced flame retardant filler can effectively reduce the risk of cracks, prevent the outer sheath layer from cracking, and extend the service life. The glycine and diethyl 2-bromoethylphosphonate grafted on the surface of the enhanced flame retardant filler can form a nitrogen-phosphorus synergistic flame retardant system, which can give the outer sheath composite material additional flame retardant properties. Zirconia fiber, as a matrix, has excellent thermal stability. After surface modification, it is added to the outer sheath composite material as a reinforced flame retardant filler. It can be evenly dispersed in the composite material, which helps to improve the thermal conductivity of the outer sheath layer. In general, this enhanced flame retardant filler plays a key role in improving the mechanical properties, high temperature resistance, thermal conductivity and flame retardancy of wires and cables. At the same time, it can effectively prevent the cracking of the material and increase the service life. It has important application value for wires and cables in fire power supply occasions.
[0012] Preferably, the method for preparing the modified thermally conductive filler comprises the following steps: S41, dispersing 10 parts of boron nitride nanosheets in 10 parts of 75% ethanol aqueous solution by weight, obtaining a boron nitride suspension after ultrasonic dispersion, adding 10 parts of tannic acid and 0.5 parts of vinyltriethoxysilane to the boron nitride suspension, mixing and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain modified boron nitride nanosheets for standby use; S42. Disperse 10 parts of modified boron nitride nanosheets and 20 parts of graphene oxide in 500 parts of nanocellulose solution with a mass concentration of 0.6% and disperse them by ultrasonic to obtain a filler mixture; vacuum freeze-dry the filler mixture at 60° C. for 24 hours to obtain a modified thermally conductive filler.
[0013] By adopting the above technical scheme, these steps and techniques not only help to improve the thermal conductivity and flame retardant properties of the material, but also promote the formation of a carbon layer during the combustion of the material, and play an effective barrier role. Boron nitride nanosheets are dispersed in an ethanol aqueous solution and ultrasonically dispersed, and then tannic acid and vinyl triethoxysilane are added for reaction. The reaction of tannic acid and vinyl triethoxysilane helps to form new chemical bonds and structures on the surface of boron nitride nanosheets, thereby improving its dispersibility and stability in the polymer matrix. Composite of graphene oxide and modified boron nitride nanosheets: The modified boron nitride nanosheets and graphene oxide are dispersed in a nanocellulose solution and ultrasonically dispersed. This composite method helps to form a good thermal conductive network structure, and the synergistic effect of graphene oxide and boron nitride nanosheets can significantly improve the thermal conductivity and flame retardant properties of the material. Vacuum freeze-drying the filler mixture can effectively remove the solvent and maintain the microstructure and morphology of the filler. This treatment method helps to improve the dispersibility and uniformity of the filler in the polymer matrix, thereby improving the overall performance of the material. The application of these steps and technologies enables the modified thermally conductive filler to exhibit excellent thermal conductivity, high temperature resistance and flame retardancy when preparing the outer sheath layer. At the same time, these materials can promote the formation of a carbon layer during the combustion process, play an effective barrier role, and improve the flame retardancy of the material. In addition, the synergistic effect of modified boron nitride nanosheets and graphene oxide can also significantly inhibit the heat release and smoke release of the material, reducing the risk of fire. Therefore, this method for preparing a modified thermally conductive filler is of great significance for improving the safety and reliability of fire-fighting power cables.
[0014] Preferably, the coupling agent is prepared by mixing vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane and γ-chloropropyltriethoxysilane in a mass ratio of 3:4:3.
[0015] By adopting the above technical scheme, the coupling agent can improve the interfacial compatibility between different materials, so that various materials can be better combined together, thereby improving the overall performance of the composite material. The coupling agent can enhance the adhesion between the materials, so that the composite material is not easy to peel off when subjected to external force, thereby improving the mechanical strength of the composite material. The coupling agent can reduce the internal stress inside the composite material, reduce the cracks caused by internal stress, and thus improve the service life of the composite material. The synergistic effect between vinyl triethoxysilane, vinyl tri (β-methoxyethoxy) silane and γ-chloropropyl triethoxy silane is mainly reflected in the following aspects: the three coupling agents each have different chemical structures and properties, and they can complement each other together to form a more stable composite system. When these three coupling agents are used together, a synergistic effect can be produced, so that the performance of the composite material is further improved. In short, the coupling agent is prepared by mixing vinyl triethoxy silane, vinyl tri (β-methoxyethoxy) silane and γ-chloropropyl triethoxy silane in a mass ratio of 3:4:3. This coupling agent has a significant effect in improving interface compatibility, enhancing adhesion and reducing internal stress. At the same time, the three coupling agents have a synergistic effect, which further improves the comprehensive performance of the composite material.
[0016] Preferably, the cross-linking agent is prepared by mixing triallyl isocyanurate and trimethallyl isocyanate in a mass ratio of 2:1.
[0017] Preferably, the antioxidant is prepared by mixing antioxidant 1076 and antioxidant 168 in a mass ratio of 2:3.
[0018] Preferably, the lubricant is one of glyceryl stearate, zinc stearate and calcium stearate.
[0019] Preferably, the vulcanizing agent is sulfur; and the accelerator is accelerator TMTD.
[0020] In a second aspect, the present application provides a method for preparing a highly flexible low-smoke fire-fighting power cable, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned high-flexibility low-smoke fire-fighting power cable, comprising the following steps: S101, twisting 12-14 tinned copper wires with a wire diameter of 0.8-1.0 mm to obtain a copper core, coating the surface of the copper core with a low-density polyethylene film with a thickness of 0.05 mm to form an insulating layer, and twisting the copper core with the insulating layer to form a cable core; S102, wrapping an aluminum foil with a thickness of 0.16 mm around the surface of the cable core to form a shielding layer, thereby obtaining a semi-finished cable; S103, adding methyl vinyl silicone rubber, ethylene propylene diene monomer rubber, linear low-density polyethylene, crosslinking agent, flame retardant, reinforced flame retardant filler, modified thermal conductive filler, coupling agent, antioxidant and lubricant into a plasticizer according to their weight proportions, protecting with nitrogen, controlling the temperature at 50-55° C., stirring at a speed of 40-50 rpm, stirring and mixing for 30-40 minutes to obtain a rubber compound; S104, transferring the mixed rubber to an open mixer according to the mass fraction, adding a vulcanizing agent and an accelerator to mix, extruding and shaping, and vulcanizing and molding at 182° C. to obtain an outer sheath composite material; S105, melt-extrude the outer sheath composite material and coat it on the surface of the semi-finished cable, cool and solidify it to form an outer sheath layer, and obtain a high-flexibility low-smoke fire-fighting power cable.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. Improved mechanical properties: Through specific material formulation and structural design, such as the use of modified zirconia fiber, the tensile strength and toughness of the outer sheath layer are improved, so that it can better withstand the external load when impacted or cracked, reducing the risk of cracks.
[0022] 2. Enhanced thermal conductivity: The synergistic effect of modified boron nitride nanosheets and graphene oxide significantly improves the thermal conductivity of the outer sheath layer. This efficient thermal conduction path helps to quickly conduct and dissipate heat, reducing the risk of local overheating.
[0023] 3. Improved flame retardancy: The use of modified magnesium hydroxide improves the flame retardancy and smoke suppression effect of the outer sheath layer. At the same time, the synergistic effect of modified boron nitride nanosheets and graphene oxide further enhances the flame retardancy and reduces the heat release and smoke release rates.
[0024] 4. High temperature resistance: Through specific material selection and modification treatment, such as the use of modified boron nitride nanosheets and graphene oxide, the high temperature resistance of the outer sheath layer is improved, enabling it to maintain stable performance in high temperature environments.
[0025] 5. Improved safety: The use of modified magnesium hydroxide not only improves the flame retardant properties, but also reduces the smoke release rate through its synergistic effect with boron nitride nanosheets, thereby effectively preventing the spread of fire when a fire occurs, reducing fire losses, and maintaining life and property safety. DETAILED DESCRIPTION
[0026] The embodiments of the present application will be described in detail below in conjunction with the examples, but those skilled in the art will understand that the following examples are only used to illustrate the present application and should not be considered to limit the scope of the present application. If the specific conditions are not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. Nanocellulose solution: JK-R0757, purchased from Shanghai Jingkang Bioengineering Co., Ltd.; antioxidant 1076 and antioxidant 168 were purchased from BASF, Germany.
[0027] In the following examples and preparation examples, 1 part means 50 g.
[0028] Preparation Example 1 Preparation of modified magnesium hydroxide The preparation method of modified magnesium hydroxide comprises the following steps: S21. According to their weight percentages, 100 parts of magnesium hydroxide, 100 parts of titanium isopropoxide, 7 parts of sodium dodecyl sulfate and 6 parts of ammonia water are placed in 400 parts of distilled water and mixed, stirred at 25° C. for 1.2 hours in a reactor, then heated to 60° C. at a rate of 5° C. / min, stirred and reacted for 5 hours, cooled and filtered; then calcined at 200° C. for 2 hours in a muffle furnace, cooled to room temperature, and obtained a solid A with porous titanium dioxide nanoparticles in situ grown on the surface of magnesium hydroxide; S22. According to the mass fractions, 150 parts of solid A were placed in a reactor with nitrogen protection, 200 parts of tetrahydrofuran were added and stirred for 2.3 hours, then 100 parts of diphenylphosphinoyl chloride tetrahydrofuran solution with a concentration of 0.05 g / mL was added dropwise at a rate of 15 mL / min, and the temperature was raised to 53°C at a rate of 4°C / min. The mixture was stirred and reacted for 7 hours, cooled and filtered, and dried to obtain modified magnesium hydroxide.
[0029] Preparation Example 2 Preparation of reinforced flame retardant filler The preparation method of the reinforced flame retardant filler comprises the following steps: S31, according to the mass fraction, placing 10 parts of zirconia fiber in 500 parts of xylene, ultrasonically dispersing for 30 minutes, adding 10 parts of glycine, refluxing for 12 hours, filtering, washing and drying to obtain pretreated zirconia fiber; S32. According to the mass proportions, place 10 parts of pretreated zirconia fibers in 500 parts of tetrahydrofuran, ultrasonically disperse for 45 minutes, and place in an ice bath at 0°C. Add 8 parts of diethyl 2-bromoethylphosphonate and 0.8 parts of N,N-diethylethylamine, and stir well for 6.7 hours. After filtering, washing, and drying, a reinforced flame-retardant filler is obtained.
[0030] Preparation Example 3 Preparation of modified thermal conductive filler The preparation method of the modified thermal conductive filler comprises the following steps: S41, dispersing 10 parts of boron nitride nanosheets in 10 parts of 75% ethanol aqueous solution by weight, obtaining a boron nitride suspension after ultrasonic dispersion, adding 10 parts of tannic acid and 0.5 parts of vinyltriethoxysilane to the boron nitride suspension, mixing and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain modified boron nitride nanosheets for standby use; S42. Disperse 10 parts of modified boron nitride nanosheets and 20 parts of graphene oxide in 500 parts of nanocellulose solution with a mass concentration of 0.6% and disperse them by ultrasonic to obtain a filler mixture; vacuum freeze-dry the filler mixture at 60° C. for 24 hours to obtain a modified thermally conductive filler. Example 1
[0031] Preparation of outer sheath composite material The outer sheath layer includes the following raw materials by weight: 60 parts of methyl vinyl silicone rubber, 12 parts of ethylene propylene rubber, 8 parts of linear low-density polyethylene, 5 parts of a cross-linking agent, 20 parts of modified magnesium hydroxide, 6 parts of a reinforced flame-retardant filler, 20 parts of a modified thermal conductive filler, 1.2 parts of a coupling agent, 1.3 parts of an antioxidant, 3 parts of glyceryl stearate, 2 parts of sulfur, and 0.6 parts of a promoter TMTD. The coupling agent is prepared by mixing vinyl triethoxysilane, vinyl tri(β-methoxyethoxy) silane, and γ-chloropropyl triethoxysilane in a weight ratio of 3:4:3. The cross-linking agent is prepared by mixing triallyl isocyanurate and trimethallyl isocyanate in a weight ratio of 2:1. The antioxidant is prepared by mixing antioxidant 1076 and antioxidant 168 in a weight ratio of 2:3. The method for preparing the outer sheath composite material comprises the following steps: S103, adding methyl vinyl silicone rubber, ethylene propylene diene monomer rubber, linear low-density polyethylene, crosslinking agent, modified magnesium hydroxide, reinforced flame retardant filler, modified thermal conductive filler, coupling agent, antioxidant and stearyl glycerol into a plasticizer according to their mass fractions, protecting with nitrogen, controlling the temperature at 50° C., stirring at a speed of 40 rpm, stirring and mixing for 40 minutes to obtain a rubber mixture; S104, according to the mass fraction, the mixed rubber is transferred to an open mixing mill, sulfur and accelerator TMTD are added and mixed, and the mixed rubber is extruded and shaped, and vulcanized at 182° C. to obtain an outer sheath composite material. Example 2
[0032] Preparation of outer sheath composite material The outer sheath layer comprises the following raw materials, calculated by weight: 65 parts of methyl vinyl silicone rubber, 15 parts of ethylene propylene rubber, 10 parts of linear low-density polyethylene, 6 parts of a cross-linking agent, 22 parts of modified magnesium hydroxide, 8 parts of a reinforced flame-retardant filler, 25 parts of a modified thermally conductive filler, 1.5 parts of a coupling agent, 1.5 parts of an antioxidant, 3.5 parts of glyceryl stearate, 2.5 parts of sulfur, and 0.8 parts of a promoter TMTD, wherein the coupling agent is prepared by mixing vinyl triethoxysilane, vinyl tri(β-methoxyethoxy) silane, and γ-chloropropyl triethoxysilane in a weight ratio of 3:4:3, the cross-linking agent is prepared by mixing triallyl isocyanurate and trimethallyl isocyanate in a weight ratio of 2:1, and the antioxidant is prepared by mixing antioxidant 1076 and antioxidant 168 in a weight ratio of 2:3; The method for preparing the outer sheath composite material comprises the following steps: S103, adding methyl vinyl silicone rubber, ethylene propylene diene monomer rubber, linear low-density polyethylene, crosslinking agent, modified magnesium hydroxide, reinforced flame retardant filler, modified thermal conductive filler, coupling agent, antioxidant and stearyl glycerol into a plasticizer according to their mass fractions, protecting with nitrogen, controlling the temperature at 55° C., stirring at a speed of 50 rpm, stirring and mixing for 30 minutes to obtain a rubber mixture; S104, according to the mass fraction, the mixed rubber is transferred to an open mixing mill, sulfur and accelerator TMTD are added and mixed, and the mixed rubber is extruded and shaped, and vulcanized at 182° C. to obtain an outer sheath composite material. Example 3
[0033] Preparation of outer sheath composite material The outer sheath layer comprises the following raw materials, calculated by weight: 63 parts of methyl vinyl silicone rubber, 14 parts of ethylene propylene rubber, 9 parts of linear low-density polyethylene, 5.6 parts of a cross-linking agent, 21 parts of modified magnesium hydroxide, 7 parts of a reinforced flame-retardant filler, 23 parts of a modified thermally conductive filler, 1.4 parts of a coupling agent, 1.4 parts of an antioxidant, 3.2 parts of glyceryl stearate, 2.3 parts of sulfur, and 0.7 parts of a promoter TMTD, wherein the coupling agent is prepared by mixing vinyl triethoxysilane, vinyl tri(β-methoxyethoxy) silane, and γ-chloropropyl triethoxysilane in a weight ratio of 3:4:3, the cross-linking agent is prepared by mixing triallyl isocyanurate and trimethallyl isocyanate in a weight ratio of 2:1, and the antioxidant is prepared by mixing antioxidant 1076 and antioxidant 168 in a weight ratio of 2:3; The method for preparing the outer sheath composite material comprises the following steps: S103, adding methyl vinyl silicone rubber, ethylene propylene diene monomer rubber, linear low-density polyethylene, cross-linking agent, modified magnesium hydroxide, reinforced flame retardant filler, modified thermal conductive filler, coupling agent, antioxidant and stearyl glycerol into a plasticizer according to their mass fractions, protecting with nitrogen, controlling the temperature at 53° C., stirring at a speed of 45 rpm, stirring and mixing for 35 minutes to obtain a rubber mixture; S104, according to the mass fraction, the mixed rubber is transferred to an open mixing mill, sulfur and accelerator TMTD are added and mixed, and the mixed rubber is extruded and shaped, and vulcanized at 182° C. to obtain an outer sheath composite material.
[0034] Comparative Example 1 The same as Example 3, except that: an equal amount of thermally conductive filler (prepared by mixing boron nitride nanosheets and graphene oxide in a mass ratio of 1:2) is used instead of the modified thermally conductive filler.
[0035] Comparative Example 2 The same as Example 3, except that an equal amount of zirconium oxide fibers are used instead of the reinforcing flame retardant filler.
[0036] Comparative Example 3 The same as Example 3, except that an equal amount of magnesium hydroxide is used instead of modified magnesium hydroxide.
[0037] Comparative Example 4 The same as Example 3, except that: the coupling agent is vinyl triethoxy silane.
[0038] Comparative Example 5 The same as Example 3, except that: the coupling agent is vinyl tris (β-methoxyethoxy) silane.
[0039] Comparative Example 6 The same as Example 3, except that: the coupling agent is γ-chloropropyltriethoxysilane.
[0040] Performance testing The outer sheath composite materials prepared in the above-mentioned Examples 1 to 3 and Comparative Examples 1 to 6 were sampled and injection-molded into test bars, and the following tests were performed. The results are shown in Table 1.
[0041] Tensile strength and elongation at break: tested according to GB / T1040-2006 standard, with a tensile rate of 50 mm / min; Thermal conductivity: Tested in accordance with ASTM D5470; Flame retardant performance (limiting oxygen index): According to GB / T2406.2-2009 standard test, the limiting oxygen index of the sample is measured using an oxygen index meter, and the sample size is 100mm*6.5mm*3.2mm; Flame retardant and low smoke performance: According to the ISO5660-1 standard test, the heat source irradiation power used is 35kW / m, the sample size is 100mm×l0mm×3mm, and the 6810 cone calorimeter test can test the heat release rate and smoke release rate of the sample during the combustion process as the combustion time increases, and calculate its maximum heat release rate and maximum smoke release rate.
[0042] Table 1 Performance test
[0043] Analyzing the data in Table 1, we can see that: 1) The outer sheath composite materials prepared in Examples 1 to 3 have excellent mechanical strength, toughness, thermal conductivity, high temperature resistance and flame retardancy, and also have good smoke suppression effects, with lower heat release rates and smoke release rates.
[0044] 2) The performance comparison analysis of the outer sheath composite material obtained by Example 3 and Comparative Example 1 shows that in the preparation process of the modified thermally conductive filler, the boron nitride nanosheets are dispersed in an ethanol aqueous solution and ultrasonically dispersed, and then tannic acid and vinyl triethoxysilane are added for reaction. The reaction of tannic acid and vinyl triethoxysilane helps to form new chemical bonds and structures on the surface of the boron nitride nanosheets, thereby improving its dispersibility and stability in the polymer matrix. Composite of graphene oxide and modified boron nitride nanosheets: The modified boron nitride nanosheets and graphene oxide are dispersed in a nanocellulose solution and ultrasonically dispersed. This composite method helps to form a good thermal conductive network structure, and the synergistic effect of graphene oxide and boron nitride nanosheets can significantly improve the thermal conductivity and flame retardant properties of the material. The filler mixture is subjected to vacuum freeze-drying treatment, which can effectively remove the solvent and maintain the microstructure and morphology of the filler. The modified thermally conductive filler can exert excellent thermal conductivity, high temperature resistance and flame retardant properties when preparing the outer sheath layer. At the same time, these materials can promote the formation of a carbon layer during the combustion process, play an effective barrier role, and improve the flame retardant properties of the material. In addition, the synergistic effect of modified boron nitride nanosheets and graphene oxide can also significantly inhibit the heat and smoke release of the material, reducing the risk of fire.
[0045] 3) The performance comparison analysis of the outer sheath composite material obtained in Example 3 and Comparative Example 2 shows that the prepared reinforced flame retardant filler reacts with the hydroxyl group on the surface of the zirconia fiber through the carboxyl group in the glycine structure to obtain a modified zirconia fiber with an amino group, and then under the action of N,N-diethylethylamine, the amino group on the surface of the modified zirconia fiber reacts with the active bromine in the structure of diethyl 2-bromoethylphosphonate to undergo a nucleophilic substitution reaction to obtain a reinforced flame retardant filler. This kind of reinforced flame-retardant filler uses zirconium oxide fiber as a matrix, has light capacity, long service life, high tensile strength, and excellent thermal stability. After surface modification, it is added to the outer sheath composite material as a reinforced flame-retardant filler and can be evenly dispersed in the composite material. When the outer sheath layer is impacted and cracks are generated, the reinforced flame-retardant filler can withstand the external load like a bridge, and bridge between the cracks, consuming the external load to do work, thereby improving the toughness of the outer sheath layer, reducing the risk of cracks, effectively preventing the outer sheath layer from cracking, and extending the service life of the outer sheath. The glycine and 2-bromoethylphosphonic acid diethyl grafted on its surface can also form a nitrogen-phosphorus synergistic flame-retardant system, which additionally gives the outer sheath composite material flame-retardant properties. When a fire occurs, it can effectively prevent the spread of fire, reduce fire losses, and maintain life and property safety.
[0046] 4) The performance comparison analysis of the outer sheath composite material obtained by Example 3 and Comparative Example 3 shows that the preparation method of the modified magnesium hydroxide flame retardant of the present application, through the sol-gel reaction, in situ grows a layer of porous titanium dioxide nanoparticles on the surface of magnesium hydroxide, which greatly increases the number of hydroxyl groups on the surface of magnesium hydroxide and the number of sites for reaction with diphenylphosphinoyl chloride, thereby achieving a significant increase in the grafting rate of diphenylphosphinoyl chloride, which is added to the outer sheath composite material, thereby improving the flame retardant and smoke suppression properties of the outer sheath layer.
[0047] 5) The performance comparison analysis of the outer sheath composite materials prepared by Example 3 and Comparative Examples 4 to 6 shows that the coupling agent is prepared by mixing vinyl triethoxysilane, vinyl tri (β-methoxyethoxy) silane and γ-chloropropyl triethoxysilane in a mass ratio of 3:4:3. The synergistic effect between them has a significant effect on improving interface compatibility, enhancing adhesion and reducing internal stress, thereby further improving the comprehensive performance of the composite material.
[0048] The outer sheath composite materials prepared in Examples 1 to 3 are used to prepare high-flexibility low-smoke fire-fighting power cables, respectively, including the following steps: S101, twisting 13 tinned copper wires with a wire diameter of 0.9 mm to obtain a copper core, coating the surface of the copper core with a low-density polyethylene film with a thickness of 0.05 mm to form an insulating layer, and twisting the copper core with the insulating layer to form a cable core; S102, wrapping an aluminum foil with a thickness of 0.16 mm around the surface of the cable core to form a shielding layer, thereby obtaining a semi-finished cable; S105, melt-extrude the outer sheath composite material and coat it on the surface of the semi-finished cable, cool and solidify it to form an outer sheath layer, and obtain a high-flexibility low-smoke fire-fighting power cable.
[0049] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A highly flexible low-smoke fire-fighting power cable, characterized in that: From the inside to the outside, it includes a cable core, a shielding layer and an outer sheath layer in sequence; the cable core is made by coating a copper core with a low-density polyethylene film; the shielding layer is made by coating a cable core with an aluminum foil; the outer sheath layer includes the following raw materials by mass: 60-65 parts of methyl vinyl silicone rubber, 12-15 parts of ethylene propylene rubber, 8-10 parts of linear low-density polyethylene, 5-6 parts of a cross-linking agent, 20-22 parts of a flame retardant, 6-8 parts of a reinforced flame retardant filler, 20-25 parts of a modified thermal conductive filler, 1.2-1.5 parts of a coupling agent, 1.3-1.5 parts of an antioxidant, 3-3.5 parts of a lubricant, 2-2.5 parts of a vulcanizing agent, and 0.6-0.8 parts of an accelerator, wherein the modified thermal conductive filler includes modified boron nitride nanosheets, nanocellulose, and graphene oxide; the flame retardant is modified magnesium hydroxide; The preparation method of the modified magnesium hydroxide comprises the following steps: S21. According to the mass fractions, 100 parts of magnesium hydroxide, 100 parts of titanium isopropoxide, 7 parts of sodium dodecyl sulfate and 6 parts of ammonia water are placed in 400 parts of distilled water and mixed, and stirred at 25° C. for 1-2 hours in a reactor, and then heated to 60° C. at a rate of 4-6° C. / min, and continued to stir and react for 4-6 hours, and cooled and filtered; then calcined at 200° C. for 2 hours in a muffle furnace, and cooled to room temperature to obtain a solid A with porous titanium dioxide nanoparticles in situ grown on the surface of magnesium hydroxide; S22. According to the mass fractions, 150 parts of solid A are placed in a reactor with nitrogen protection, 200 parts of tetrahydrofuran are added and stirred for 2-3 hours, then 100 parts of diphenylphosphinoyl chloride tetrahydrofuran solution with a concentration of 0.05 g / mL is added dropwise at a rate of 15 mL / min, the temperature is raised to 53°C at a rate of 4°C / min, stirring and reacting are continued for 7 hours, cooled and filtered, and dried to obtain modified magnesium hydroxide.
2. According to claim 1, a highly flexible low-smoke fire-fighting power cable is characterized in that: The method for preparing the reinforced flame retardant filler comprises the following steps: S31, according to the mass fraction, placing 10 parts of zirconia fiber in 500 parts of xylene, ultrasonically dispersing for 30 minutes, adding 10 parts of glycine, refluxing for 12 hours, filtering, washing and drying to obtain pretreated zirconia fiber; S32. According to the mass proportions, place 10 parts of pretreated zirconia fibers in 500 parts of tetrahydrofuran, ultrasonically disperse for 40-50 minutes, ice-bath at 0°C, add 8 parts of diethyl 2-bromoethylphosphonate and 0.8 parts of N,N-diethylethylamine, stir well for 6-7 hours, filter, wash and dry to obtain the reinforced flame retardant filler.
3. According to claim 1, a highly flexible low-smoke fire-fighting power cable is characterized in that: The preparation method of the modified thermal conductive filler comprises the following steps: S41, dispersing 10 parts of boron nitride nanosheets in 10 parts of 75% ethanol aqueous solution by weight, obtaining a boron nitride suspension after ultrasonic dispersion, adding 10 parts of tannic acid and 0.5 parts of vinyltriethoxysilane to the boron nitride suspension, mixing and stirring to react, and after the reaction is completed, filtering, washing and drying to obtain modified boron nitride nanosheets for standby use; S42. Disperse 10 parts of modified boron nitride nanosheets and 20 parts of graphene oxide in 500 parts of nanocellulose solution with a mass concentration of 0.6% and disperse them by ultrasonic to obtain a filler mixture; vacuum freeze-dry the filler mixture at 60° C. for 24 hours to obtain a modified thermally conductive filler.
4. According to claim 1, a highly flexible low-smoke fire-fighting power cable is characterized in that: The coupling agent is prepared by mixing vinyl triethoxysilane, vinyl tri (β-methoxyethoxy) silane and γ-chloropropyl triethoxy silane in a mass ratio of 3:4:
3.
5. According to claim 1, a highly flexible low-smoke fire-fighting power cable is characterized in that: The cross-linking agent is prepared by mixing triallyl isocyanurate and trimethallyl isocyanate in a mass ratio of 2:
1.
6. A highly flexible low-smoke fire-fighting power cable according to claim 1, characterized in that: The antioxidant is prepared by mixing antioxidant 1076 and antioxidant 168 in a mass ratio of 2:
3.
7. A highly flexible low-smoke fire-fighting power cable according to claim 1, characterized in that: The lubricant is one of glyceryl stearate, zinc stearate and calcium stearate.
8. The high-flexibility low-smoke fire-fighting power cable according to claim 1, characterized in that: The vulcanizing agent is sulfur; the accelerator is accelerator TMTD.
9. A method for preparing a high-flexibility low-smoke fire-fighting power cable as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S101, preparing a cable core: twisting 12-14 tinned copper wires with a wire diameter of 0.8-1.0 mm to obtain a copper core, coating the surface of the copper core with a low-density polyethylene film with a thickness of 0.05 mm to form an insulating layer, and twisting the copper core with the insulating layer to form a cable core; S102, preparing a shielding layer: wrapping an aluminum foil with a thickness of 0.16 mm around the surface of the cable core to form a shielding layer, and obtaining a semi-finished cable; S103, prepare outer sheath composite material: according to the mass fraction, add methyl vinyl silicone rubber, ethylene propylene diene monomer rubber, linear low density polyethylene, crosslinking agent, flame retardant, reinforced flame retardant filler, modified thermal conductive filler, coupling agent, antioxidant and lubricant into a plasticizer, protect with nitrogen, control the temperature at 50-55°C, stir at a speed of 40-50rpm, stir and mix for 30-40min to obtain a rubber mix; then transfer the rubber mix to an open mixing mill, add a vulcanizing agent and an accelerator to mix, extrude and shape, and vulcanize at 182°C to obtain an outer sheath composite material; S104, melt-extrude the outer sheath composite material and coat it on the surface of the semi-finished cable, cool and solidify it to form an outer sheath layer, and obtain a high-flexibility, low-smoke fire-fighting power cable.
Citation Information
Patent Citations
Magnesium phosphide flame retardant as well as preparation method and application thereof
CN116948257A
Flame-retardant wire and cable silicone rubber and preparation method thereof
CN117004234A
Fiber-reinforced fluoroplastic wire cable and manufacturing method thereof
CN117524563A
High-flexibility low-smoke modified power cable based on fluoropolymer sheath and preparation method
CN117976314A
Flame-retardant silicone rubber cable sheath material and preparation method thereof
CN119081420A
Cited By
High-flame-retardant cable and preparation method thereof
CN120636964A
A highly flame retardant cable and a method for producing the same
CN120636964B
Wear-resistant flame-retardant transfer coating as well as preparation method and application thereof
CN122146124A